SMART CITY-BASED TOURISM DEVELOPMENT IN SURABAYA'S OLD TOWN - Sildjian, Audri; Haryati, Eny (International Journal of Multidisciplinary Reseach, 2026)
The development of heritage tourism areas requires an approach that focuses not only on physical preservation, but also on governance, technology utilization, and regional sustainability. This study aims to analyze the development of Surabaya Old Town Tourism in terms of the Smart City concept through six main pillars, namely Smart Governance, Smart Branding, Smart Economy, Smart Living, Smart Society, and Smart Environment. This study uses a qualitative descriptive approach with data collection techniques through field observations, interviews with related parties, as well as documentation and literature studies. Data analysis was carried out using the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The research results show that the development of Surabaya's Old Town Tourism has led to the implementation of the Smart City concept, although the level of implementation varies across pillars. The Smart Branding and Smart Economy pillars show relatively strong achievements through digital promotion, cultural events, and the growth of MSMEs and creative economy activities. The Smart Governance pillar has been supported by regional revitalization policies and the use of digital services, but has not been fully integrated. Meanwhile, the implementation of Smart Living, Smart Society, and Smart Environment still faces several challenges, particularly in terms of regional security, the sustainability of community participation, and the limited green space and shading elements. Overall, the six Smart City pillars are interconnected and form a heritage tourism area management system, so a more integrated, sustainable, and participatory development strategy is needed to increase the competitiveness of Surabaya's Old Town Tourism.